2020
DOI: 10.1097/iop.0000000000001564
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Histopathologic Evaluation and Clinical Correlation for Isolated Congenital Myogenic Ptosis and Aponeurotic Ptosis

Abstract: Purpose: To evaluate light microscopy and transmission electron microscopy findings of levator muscle/aponeurosis materials and their correlation with clinical findings in isolated congenital myogenic and aponeurotic blepharoptosis. Methods: Demographic and clinical data were obtained from patients. Qualitative and quantitative evaluations for muscle fiber morphology were performed using light microscopy and transmission electron microscopy on tissue sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Similar results were reported in a previous study [ 18 ]. Previous research reported a decreased amount of striated muscle and fiber damage indicators in aponeuroses obtained from patients with simple congenital ptosis [ 34 ]. Heisel et al [ 31 ] reported histological disorganization and fibrosis in the orbital septum of patients with congenital ptosis and poor levator function.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported in a previous study [ 18 ]. Previous research reported a decreased amount of striated muscle and fiber damage indicators in aponeuroses obtained from patients with simple congenital ptosis [ 34 ]. Heisel et al [ 31 ] reported histological disorganization and fibrosis in the orbital septum of patients with congenital ptosis and poor levator function.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, most patients with blepharoptosis have abnormal structure or function of levator aponeurosis. 2 Pathologically, the main manifestations are varying degrees of injury or degeneration of levator aponeurosis such as thinning, elongation, rupture, breaking, and curling. Light microscope shows collagen degeneration, fat infiltration or fibrosis in the lesion of aponeurosis.…”
Section: Discussionmentioning
confidence: 99%
“…Light microscope shows collagen degeneration, fat infiltration or fibrosis in the lesion of aponeurosis. 2 At present, there are many kinds of correction, mainly by shortening or folding the levator aponeurosis to strengthen the strength of the levator muscle. 3 However, the operation itself does not fundamentally repair the histologic structure of the levator aponeurosis or improve its function, and only mechanically shortens or folds the aponeurosis, which may be one of the causes of postoperative recurrence and other complications.…”
mentioning
confidence: 99%
“…The ultra-thin sections were stained with uranyl acetate and lead citrate, analyzed with a TEM and attached digital camera (TEM, JEM1400, Japan, GATAN, Germany). The length and width of mitochondria (at least 50 mitochondria per section) were measured with DigitalMicrograph (Gatan Inc., USA) software 6 , 59 , 60 .…”
Section: Methodsmentioning
confidence: 99%